2015
DOI: 10.1002/esp.3845
|View full text |Cite
|
Sign up to set email alerts
|

Impact of draining hilly lands on runoff and on‐site erosion: a case study from humid Ethiopia

Abstract: The use of drainage ditches on farmland has an impact on erosion processes both on-site and off-site, though their environmental impacts are not unequivocal. Here we study the runoff response and related rill erosion after installing drainage ditches and assess the effects of stone bunds in north Ethiopia. Three different land management systems were studied in 10 cropland catchments around Wanzaye during the rainy season of 2013: (1) the exclusive use of drainage ditches (locally called feses), (2) the exclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…At the same time, as we saw in our study for gullies RV1 in 2014 and C5 in 2016, fesses built in the uplands for carrying of excess rainfall from agricultural land directly contribute to gully advancement (Table 2). Monsieurs et al [40] had similar observations in the Wanzaye watershed, Northern Ethiopia. Therefore, aspirational watershed management practices require integration of upland and downstream practices that include gully control.…”
Section: Discussionmentioning
confidence: 60%
“…At the same time, as we saw in our study for gullies RV1 in 2014 and C5 in 2016, fesses built in the uplands for carrying of excess rainfall from agricultural land directly contribute to gully advancement (Table 2). Monsieurs et al [40] had similar observations in the Wanzaye watershed, Northern Ethiopia. Therefore, aspirational watershed management practices require integration of upland and downstream practices that include gully control.…”
Section: Discussionmentioning
confidence: 60%
“…This flow found its way through a shrink/swell soil crack that was subsequently eroded and formed the gully channel. Similarly, Monsieurs et al (2015) reported at the Wanzaye catchment the concentration of flow initiated gullies. In the Debre Mawi catchment, Dagnew et al (2015) reported that infiltration furrows, which were located in soils that were periodically saturated, intercepted the interflow resulting initiation of gullies by the concentrated flow.…”
Section: Effect Of Shrink/swell Cracksmentioning
confidence: 66%
“…Land and water management includes soil and water conservation practices (SWC) and reservoir constructions, which also have a significant impact on hydrological processes. Soil and water conservation (SWC) decreased surface runoff [80,88] and sediment concentration [80]. Furthermore, Akale, et al [80] noticed that conservation practices increased baseflow by 45% in Guale and 81% in Tikur-Wuha.…”
Section: Modelling Approaches Of Studies In the Lake Tana Basinmentioning
confidence: 99%